Hubungan Pengetahuan Ibu Dan Perilaku Pemberian Bedak Bayi Dengan Kejadian Ruam Popok Pada Bayi - Maharani, Indri; Mariana, Silvia; Susanti, Desy; Monica, Olivia Tri (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
According to the World Health Organization (WHO), diaper rash in infants is 25% of the 6,840,507,000 babies born worldwide in 2017. Meanwhile, the incidence of diaper rash or diaper rash in Indonesia has at least 22 million children under the age of five, where 7-35% of them affect both boys and girls. under three years of age and reach 10% of the population of 220-240 million. Purpose of Conducting Research To determine the relationship between mother's knowledge and behavior of giving baby powder with the incidence of diaper rash in infants at PMB Miftahul Jannah. This research method is qualitative with a cross sectional approach. With a population of 34 respondents, all mothers who experienced the incidence of dim pmb miftahul jannah diaper rash. research design in this study is to use a questionnaire sheet. The sample data collection technique is 34 respondents. Data analysis uses chi-square (cross table). The results of this study found that there is a relationship with knowledge (p-0.026). The behavior of giving powder (p=0.020), with the incidence of diaper rash in infants with preeclampsia at Miftahul Jannah PMB found a relationship, namely knowledge (p=0.026), behavior (p=0.020).